PERLINDUNGAN KONSUMEN TERHADAP PENGGUNA PINJAMAN ONLINE ILEGAL DI KOTA DENPASAR - Oktha Wardi Purba; Si Ngurah Ardhya; Komang Febrinayanti Dantes (Jurnal Ilmu Hukum Sui Generis, 2023)
This research aims to (1) analyze legal protection for online loan consumers in terms of inappropriate information in advertisements regarding loan interest; and (2) knowing and analyzing the role and function of the OJK in providing consumer protection for illegal online loans in Denpasar City. The type of research in writing this thesis is empirical juridical which is analyzed qualitatively. The data used in this research are primary data and secondary data. Primary data is obtained from the first source, secondary data from primary, secondary and tertiary legal materials. Data collection techniques use interview techniques and document study. Meanwhile, the sampling technique in this research is non-probability sampling, which is purposive sampling. Based on the research results, it was found that (1) consumer protection regarding illegal online loans is carried out preventively and repressively through Law Number 21 of 2011 and business actors are required to pay attention to and implement the provisions of OJK regulation no. 77/POJK.07/2016; (2) The OJK's role in protecting consumers of illegal online loans in Denpasar City is carried out by providing education and literacy to the community, collaborating with the ministry and the Central OJK by forming the SWI SATGAS, updating official fintech lending data, and facilitating the public to send complaints via the website OJK APPK.